Life-threatening bradycardia in an anorexia nervosa patient: A case report - Alexandra W. Obremskey; Janis L. Sethness; Tarane Shafi; Thomas V. Brogan (Wolters Kluwer Medknow Publications, 2024)
Cardiac complications are frequently seen in patients with anorexia nervosa, with bradycardia being the most common. The degree of bradycardia can be a marker of disease severity as heart rate (HR) nadir is correlated with body mass index, total weight loss, and recent weight loss. Despite the prevalence and potential severity of bradycardia, there is limited literature evaluating the optimal management of severe bradycardia. This case report discusses a patient with a HR lower than previously reported in the literature and provides a valuable opportunity to examine the management of cardiac output in cases of severe bradycardia.